2020
DOI: 10.1134/s0012496620050014
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of the Multimerin-1 Gene in α-Synuclein Knokout Mice

Abstract: Multimerin-1 (Mmrn-1) is a soluble protein, also known as elastin microfibril interfacer 4 (EMI-LIN-4), found in platelets and in the endothelium of blood vessels. Its function and role in pathology are still not fully understood. Genetic modifications in alpha-synuclein gene (Snca) locus that mapped 160 Kb apart from Mmrn-1 in mouse genome, could weigh with regulatory elements of Mmrn-1 gene. We have studied the Mmrn-1 expression in brain cortex of three mouse lines with Snca knock-out: B6(Cg)-Snca tm1.2Vlb /… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
2
1
1
Order By: Relevance
“…Both SNPs affected the differential expression of SNCA transcripts and rs3910105 also affected the MMRN1 gene that is adjacent to the SNCA gene. MMRN1 is elastin microfibril interface 4 and is able to carry platelet factor V. A recent study identified that MMRN1 expression was increased in SNCA knockout mice that was attributed to the genetic modification in the SNCA locus [38]. However, our study identified regulatory link between the intronic SNP in SNCA gene and MMRN1 gene expression.…”
Section: Discussioncontrasting
confidence: 49%
“…Both SNPs affected the differential expression of SNCA transcripts and rs3910105 also affected the MMRN1 gene that is adjacent to the SNCA gene. MMRN1 is elastin microfibril interface 4 and is able to carry platelet factor V. A recent study identified that MMRN1 expression was increased in SNCA knockout mice that was attributed to the genetic modification in the SNCA locus [38]. However, our study identified regulatory link between the intronic SNP in SNCA gene and MMRN1 gene expression.…”
Section: Discussioncontrasting
confidence: 49%
“…Indeed, impaired platelet adhesion and thrombus formation observed in the C57BL/6JOlaHsd substrain was shown to be rescued by recombinant multimerin 1 infusion 53 . Interestingly, multimerin 1 expression is increased in αsyn KO mouse 54 . Other predicted genes in this region, such as Gm43864, Gm43867, and Gm18838, could also contribute to the findings attributed to the Rab27 DKO phenotype.…”
Section: Discussionmentioning
confidence: 94%
“…Both SNPs affected the differential expression of SNCA transcripts and rs3910105 also affected the MMRN1 gene that is adjacent to the SNCA gene. MMRN1 is elastin microfibril interface 4 and is able to carry platelet factor V. A recent study identified that MMRN1 expression was increased in SNCA knockout mice that was attributed to the genetic modification in the SNCA locus 36 . However, our study identified regulatory link between the intronic SNP in SNCA gene and MMRN1 gene expression.…”
Section: Discussionmentioning
confidence: 99%